Development of Peer Educators within Paraprofessional Community-Based Adult Education Models: An Experiential Learning Perspective - Megan M. Seibel; Rick D. Rudd (Adult Education Research Conference, 2014)
Research project of community-based nutrition education explored the conceptual and practical role of experience in paraprofessional educator models and focused on the situated, contextual experiences of paraprofessionals in the communities where they work and live as unique, challenging, and potentially positive for learning outcomes.